Natural Resources Management: Challenges and Way Forward - Concept Note - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
The present study “Natural Resources Management: Challenges and Way Forward for the New CGIAR – a Stripe Review” is designed to provide CGIAR leadership, centers, and donors with perspectives on the factors that influence achieving impact at scale from NRM research, sharing insights and information helpful to assist in developing quality programs.